DEVELOPING A HEALTHY LIFESTYLE FOR FUTURE TEACHERS BASED ON AESTHETIC EDUCATION - Kamchiyev Salimberdi Xudayberdiyevich (Web of Journals Publishing, 2025)
A healthy lifestyle is important for future teachers because they are key figures influencing the physical and mental health of students. This article explores the connection between aesthetic education and the healthy lifestyle of future teachers. Aesthetic education fosters an appreciation for beauty and harmony, which in turn affects individuals' choice of a balanced lifestyle. The research involves analyzing existing literature, methods of integrating aesthetic education into teacher training programs, and examining its impact on health. The results show that aesthetic education positively influences physical activity, mental health, and overall well-being.